The Relationship between Nurse Workload and Nurse Stress Level in Intensive Care Unit (ICU) - Nababan, Tiarnida (Jurnal Keperawatan Priority, 2025)
Stress is generally being experienced by most of the nurses due to the duration of working hours and the number of patients. The high workload of nurses often results in fatigue, loss of concentration at work, the ability to remember information is very limited, being emotional and apathetic. This research is an analytic survey, with cross-sectional design in which the independent and dependent variables were examined simultaneously to determine the relationship between the nurse workload and stress level of nurses in the ICU wards of Dr. Pirngadi Regional General Hospital. This study uses primary data which were obtained by using questionnaires and secondary data were obtained from the medical record, with questionnaire instruments. The entire population were nurses in the ICU wards and samples in this study consisted of 24 nurses taken by total sampling technique. Based on the results of the chi square test at work variable, it is found that the X2 count 3.154, which means there is not any relationship between working hours and the level of stress of nurses working in the ICU, and the variable of the number of patients X2 count 6,446 which means there is a relationship between number of patients with stress level for nurses in the ICU wards.The study's findings indicate that while there is a correlation between the number of patients and nurses' stress levels in the General Hospital's intensive care unit wards, there is no correlation between working hours and nurses' stress levels.